IDENTIFIKASI DAN PENETAPAN KADAR BORAKS DALAM BAKSO JAJANAN DI KOTA MANADO - Tubagus, Indra (UNIVERSITAS SAM RATULANGI, 2013)
The purpose of this study which are to identify and determine the rate of borax in meatballs snackssold in the city of Manado. Sampling locations are Bunaken, Malalayang, Mapanget, Sario, Singkil,Tikala, Tuminting and Wanea sub district. Each location is determined each 2 meatballs snacksvendors. Recruitment is done 3 times in each meatball vendor meatball snacks of 20 seeds, until atotal of 60 pieces of meatball samples in a month for each vendor. The samples were identified usinga flame test method and test turmeric paper color method. Identification experiment results of researchmeatballs with borax in the samples and test reaction flame color test please note that all samplestested meatball not harmful preservatives.Key words : Borax, flame test, color test, meatball, Manado